2015
DOI: 10.1155/2015/603182
|View full text |Cite
|
Sign up to set email alerts
|

A Classification of Basic Helix-Loop-Helix Transcription Factors of Soybean

Abstract: The complete genome sequence of soybean allows an unprecedented opportunity for the discovery of the genes controlling important traits. In particular, the potential functions of regulatory genes are a priority for analysis. The basic helix-loop-helix (bHLH) family of transcription factors is known to be involved in controlling a wide range of systems critical for crop adaptation and quality, including photosynthesis, light signalling, pigment biosynthesis, and seed pod development. Using a hidden Markov model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 62 publications
7
47
0
Order By: Relevance
“…A phylogenetic tree was constructed, based on the resulting list of bHLH TFs, to examine their evolutionary relationship between Arabidopsis and soybean (Figure S1A). Four putative proteins, named GmbHLH56 (Glyma.13G322100), GmbHLH57 (Glyma.12G178500), GmbHLH58 (Glyma.12G081200) and GmbHLH59 (Glyma.11G192800), belonging to the IIIa subgroup of the bHLH proteins (Hudson and Hudson ), were identified as potential FIT orthologs. GmbHLH300 (Glyma.03G130600), along with GmbHLH320 (Glyma.03G130400), GmbHLH321 (Glyma.19G132500) and GmbHLH322 (Glyma.19G132600), are grouped together with AtbHLH38/39/100/101.…”
Section: Resultsmentioning
confidence: 99%
“…A phylogenetic tree was constructed, based on the resulting list of bHLH TFs, to examine their evolutionary relationship between Arabidopsis and soybean (Figure S1A). Four putative proteins, named GmbHLH56 (Glyma.13G322100), GmbHLH57 (Glyma.12G178500), GmbHLH58 (Glyma.12G081200) and GmbHLH59 (Glyma.11G192800), belonging to the IIIa subgroup of the bHLH proteins (Hudson and Hudson ), were identified as potential FIT orthologs. GmbHLH300 (Glyma.03G130600), along with GmbHLH320 (Glyma.03G130400), GmbHLH321 (Glyma.19G132500) and GmbHLH322 (Glyma.19G132600), are grouped together with AtbHLH38/39/100/101.…”
Section: Resultsmentioning
confidence: 99%
“…A common response to S deficiency in most aus accessions was an increase in root length, and GWAS analysis identified one locus for which the common major haplotype increased root length, while only 17% of accessions with the minor haplotype had roots about 5% increase in length. Though these alleles appear to be the common alleles, this locus would be of little practical interest (from the agronomical/breeding point of view), candidate genes at this locus indicate the involvement in: a) regulation of growth in roots and flowers, and response to various stresses (helix-loop-helix transcription factor, Pires and Dolan, 2010;Hudson and Hudson, 2015); b) plant detoxification reaction during abiotic stress, like cadmium and arsenic detoxification (glutathione S-transferase, Kumar and Trivedi, 2018) and plant development (Gong et al, 2005); c) protein ubiquitination which plays roles in several plant developmental FIGURE 5 | Relative expression of sulfotransferase genes: Os11g0503900 (A) and Os11g0505300 (B) in root and leaves tissue from genotypes harboring favorable/unfavorable haplotypes for total dry matter. Plants were grown either under low-S or high-S condition.…”
Section: Discussionmentioning
confidence: 99%
“…Many other candidate genes were identified that are associated with the variation of number of pods per plants. Among the candidate genes, basic helixloop-helix (bHLH) DNA-binding superfamily protein that is involved in the development and dehiscence of seed and pod (Hudson and Hudson, 2015), protein kinase superfamily protein is involved in pollen abortion (Radchuk et al, 2006), pyruvate kinase family protein associated with early embryo abortion of flower (Zhang et al, 2014), ARM repeat superfamily protein is involved in self-incompatibility and reduction of pod number (Sharma and Pandey, 2016), chaperone DNAJ-domain superfamily protein is involved in male sterility (Yang et al, 2009), DNAJ heat shock Nterminal domain-containing protein that increases tolerance to heat and prevents fruit drop (Zhao et al, 2015), prolinerich family protein associated with flower and pod development (Giorno et al, 2013), adenine nucleotide alpha hydrolases-like superfamily protein is involved in male sterility (Mok and Mok, 2001), homeodomain-like protein regulates anther dehiscence (Wilson et al, 2011), cytochrome P450 is involved in the pollen tube development and fertilization (Zhao et al, 2015), pyruvate kinase family protein found associated with early embryo abortion (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%